PedsQL Multiple Sclerosis Module Domain and Item Development: Qualitative Methods. (September 2021) - Gaudioso, Cristina; Oo, Samuel; Mar, Soe; Hendricks-Ferguson, Verna L.; Newland, Pamela; Varni, James W.
Background: The objective of this qualitative methods study was to develop the domains and items to support the content validity for the Pediatric Quality of Life Inventory (PedsQL) Multiple Sclerosis Module for youth with pediatric-onset multiple sclerosis. Methods: A literature review of multiple sclerosis–specific questionnaires and clinical research was conducted to generate domains. An expert panel composed of 12 neurologists who were pediatric-onset multiple sclerosis specialists provided feedback on the conceptual framework. Focus interviews with 9 youth with pediatric-onset multiple sclerosis and 6 parents were conducted to develop the relevant domains and item content from the patient and parent perspective. In the cognitive interviews phase, 9 youth with pediatric-onset multiple sclerosis and 6 parents provided feedback on item content, relevance, importance, and understandability of the pediatric-onset multiple sclerosis–specific domains and items. The final interview phase with 5 youth with pediatric-onset multiple sclerosis and 5 parents comprised a pilot testing of the new PedsQL MS Module. Results: Eighteen domains were derived from the qualitative methods with item content saturation achieved at 100 items based on 40 interviews with 23 youth with pediatric-onset multiple sclerosis aged 10-21 years and 17 parents. The domains derived include general fatigue, sleep/rest fatigue, cognitive functioning, tingling sensations, numbness sensations, physical weakness, pain, speech, balance, fine motor, vision, urination, constipation, bowel incontinence, worry, communication, treatment, and medicines. Conclusions: Qualitative methods involving 23 youth with pediatric-onset multiple sclerosis and 17 parents in the domain and item development process support the content validity for the new PedsQL MS Module. Future plans include a national field test of the PedsQL MS Module scales and items.